Sex and Electrode Configuration in Transcranial Electrical Stimulation - Russell, Michael J.; Goodman, Theodore A.; Visse, Joseph M.; Beckett, Laurel; Saito, Naomi; Lyeth, Bruce G.; Recanzone, Gregg H. (Frontiers in Psychiatry, 2017)
Transcranial electrical stimulation (tES) can be an effective non-invasive neuromodulation procedure. Unfortunately, the considerable variation in reported treatment outcomes, both within and between studies, has made the procedure unreliable for many applications. To determine if individual differences in cranium morphology and tissue conductivity can account for some of this variation, the electrical density at two cortical locations (temporal and frontal) directly under scalp electrodes were modeled using a validated MRI modeling procedure in 23 subjects (12 male and 11 female). Three different electrode configurations (non-cephalic, bi-cranial, and ring) commonly used in transcranial electrical stimulation were modeled. The aims of this study were to assess the effects of configuration and current intensity on relative current received at a cortical brain target directly under the stimulating electrode and to characterize individual variation. The different electrode configurations resulted in up to a nine-fold difference in mean current densities delivered to the brains. The ring configuration delivered the least current and the non-cephalic the most. Female subjects showed much less current to the brain than male subjects. Individual differences in the current received and differences in electrode configurations may account for significant variability in current delivered, and thus potentially a significant portion of reported variation in clinical outcomes at two commonly targeted regions of the brain.